„Co choroba, to doktor...”. O językowo-kulturowym obrazie lekarza w polszczyźnie - Skorupska-Raczyńska, Elżbieta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
Healing traditions are very likely to have roots in the beginnings of any civilisation, which comes from the natural needs of a human striving for physical and mental comfort. On ethnically Polish lands, medical culture developed together with the society, which is reflected in the names of healers. The linguistic and cultural image of a doctor is affected by the anthropocentric experiences of speakers of Polish, stereotypes and the media that strengthen its versions, all recorded in the lexis, phraseology and paremiography. Today (according to the survey), negative traits of doctors (31) are significantly more common than their virtues (9) that include: being specific, accurate, efficient, devoted to duty and caring. According to the survey, today’s doctor is, most of all, in a hurry, overworked and tired, but also dissatisfied, uninterested in the patient, impatient, late, cold and always angry. People’s focus on doctors’ negative traits has been a permanent phenomenon for centuries.